Significance of Composite Materials for Making Better Future Society - S. Ravichandran; Karandeep Kaur; Pooja (International Journal of Advance in Molecular Engineering, 2024)
Since in the beginning of human history, Materials had been started in use. We can't imagine our world without materials. In fact, Materials has taken centre position in many developed and developing countries. The materials that humans have chosen to use for engineering projects throughout history, including the Stone, Iron, and Silicon ages. However, in order to meet today's difficulties, new materials must be discovered and developed with the necessary qualities at a cost that is affordable. Materials can be utilized for a variety of tasks, such as building construction, machine manufacturing, electricity production, message transmission, and control devices. These materials come in a variety of forms, including glass, rubber, alloys, mica, iron, copper, and aluminum, as well as cement. The understanding of materials and their characteristics is crucial for an engineer with design skills. These materials come in a variety of forms, including glass, rubber, alloys, mica, iron, copper, and aluminum, as well as cement. The understanding of materials and their characteristics is crucial for an engineer with design skills. The materials used to make machine parts should have qualities appropriate for the operating environment. A design engineer also needs to be aware of the impacts that manufacturing processes have. Thus, engineering materials encompass a broad range of substances used in various industries for construction, manufacturing and other applications. Metals, such as steel and aluminum are known for their high strength and conductivity. Polymers, including plastics and rubbers, provides flexibility, lightweight and corrosion resistance, making them perfect in packaging, automotive parts and consumer goods. Composite materials came to existence in 1992 due to their improved specific mechanical properties and industry demand for high performance for construction. Nature contains a wide variety of composite materials. Wood, for instance, is a fibrous natural composite made of cellulose fiber in a lignin matrix. Bone is an additional instance of a natural composite. When compared to individual materials, composite materials are stronger, lighter, or less expensive, hence these are selected. These factors have led to the replacement of separate materials in engineering and building applications with composite materials. The use of composite almost in all fields which includes medical, electrical, aerospace, defence, transport, communication, military, sports etc., In this paper a review is being carried out on composite materials their classification and their importance in current world.
Keywords: Advancement; Composites; Importance; Material; engineering